A histopathological study and clinico histopathological correlation of single lesions in leprsoy - Shathruvedula, Ravindranath (International Journal of Medical Research and Review, 2016)
Background: Leprosy caused by Mycobacterium Leprae is an important public health concern. Single lesions in leprosy are commonly seen in TT, BT and indeterminate leprosy. Aim: The aim of the present study is to evaluate histopathological features of single lesions in different clinical types of leprosy and evaluate clinico histopathological correlation. Methods: Scalpel biopsies of single leprosy lesions from all 40 patients were done followed by staining of slides with Haemotoxilin and Eosin stains. A thorough study of histopathological features of slides was done followed clinico- histopathological correlation. Results: There were 7 cases of indeterminate leprosy, 27 cases of BT type and 6 cases of TT type clinically. There were clinico- histopathological correlations in 32.5% of the total cases. More clinico histopathological correlation was seen among TT type and least correlation was seen among BT type. Conclusion: There is clinico histopatholgical correlation in 32.5% of the total cases. More correlation is seen TT type of leprosy than in BT type of leprosy in single lesions.